Palliative Care for Neurologically Injured Patients: Why and How? - Bindu, Barkha; Rath, Girija P. (Journal of Neuroanaesthesiology and Critical Care, 2019)
The role of palliative care in patients with cancer is widely acknowledged and practiced. Though its role in chronic, progressive, and incurable neurological conditions is being recognized now, it is not widely practiced. Lack of awareness and training are important factors contributing to this. Neurological patients differ from oncological patients with respect to their symptoms, fluctuating disease course, varied prognoses, and difficulty in identifying end-of-life stage. Knowledge of different neurological conditions is important to practice neuropalliative care appropriately. Growth of neuropalliative care services must begin with the neurologist at the center of the multidisciplinary team. Neurologists need to be trained in communication skills and advance care planning, and must be aware of end-of-life care, do-not-resuscitate policies, and withdrawal of life support measures. This article elaborates on these aspects of neuropalliative care and discusses its role in various neurological conditions.
Keywords: neuropalliative care; end-of-life care; do-not-resuscitate; amyotrophic lateral sclerosis